Embedding “Profit for Purpose” in Business and Entrepreneurial Education - Fibriyani Nur Khairin; Anisa Kusumawardani; Yoremia Lestari Ginting (Jurnal Ilmiah Akuntansi, 2024)
The paradigm shift in the business and entrepreneurial environment will also have an impact on business education in universities. This study aims to explore the uniqueness of social enterprises and then integrate the values into business and entrepreneurship education through the perspective of entrepreneurship theory. The research uses qualitative methods with a case study approach to social enterprises in East Kalimantan province. The data source comes from interviews with informants who are founders and managers of social enterprises and related documents. The result, based on entrepreneurship theory, reveals that two stages can be instilled in the learning process, which is the venture and monetization stage. The process between those stages will create the social enterprise values related to value potential (opportunity), driven value (competencies), and value appropriate (entrepreneur reward that is specifically related to entrepreneur characters).